(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes the aesthetics of music as well as the beauty of music. In particular, there has been an attempt to show that musicians have a high aesthetic taste. At the same time, scholars’ opinions are quoted.